Studi Literatur Pengaruh Penambahan Bakteri Asam Laktat Dalam Pakan Formulasi Lokal Atau Pakan Komersial Terhadap Profil Mikrobiota Salmonella sp Pada Saluran Pencernaan Ayam Broiler - Yustina Indrawati; Frans U Datta; Annytha I.R Detha (Jurnal Veteriner Nusantara, 2023)
The purpose of this study was to determine the effect of adding lactic acid bacteria in local formulated or commercial feeds to the microbiota profile of Salmonella sp. in the digestive tract of broilers and to study the combination of these feeds with lactic acid bacteria in order to optimize digestion in the chickens. This literature study was conducted by searching and collecting information from various sources using the Mendeley and Google Scholar applications. The data obtained through the search was analyzed and then evaluated. Based on the results, there were effects of adding lactic acid bacteria in local feed formulations at a concentration of 107 cells/ml on fermentation of 10% husk waste, a concentration of 109 cells/ml on 0.50 g/L ginger extract, a concentration of 1.5 ml/L on raw cabbage (sauerkraut), 15% concentration on pure coconut oil waste (blondo), 100% concentration on Anacardium occidentaleor plant, Phyllanthun niruri L plant extract, Syzygium aromaticum extract, 95% concentration on Moringa oleifera leaves L, waste from tapioca starch and on commercial feeds, such as GCI 201 cs 100% and BR 1 0.075% in the form of powder, pellets, dry and liquid probiotics. Furthermore, the use of poultry feed supplemented with good lactic acid bacteria in vitro and in vivo effectively reduced the population of Salmonella sp. characterized by the presence of antimicrobial activity of the lactic acid bacteria.